If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 48 = 7x + -7 Reorder the terms: 48 + -6x = 7x + -7 Reorder the terms: 48 + -6x = -7 + 7x Solving 48 + -6x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 48 + -6x + -7x = -7 + 7x + -7x Combine like terms: -6x + -7x = -13x 48 + -13x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 48 + -13x = -7 + 0 48 + -13x = -7 Add '-48' to each side of the equation. 48 + -48 + -13x = -7 + -48 Combine like terms: 48 + -48 = 0 0 + -13x = -7 + -48 -13x = -7 + -48 Combine like terms: -7 + -48 = -55 -13x = -55 Divide each side by '-13'. x = 4.230769231 Simplifying x = 4.230769231
| (z+11)(z-11)=81 | | 8x-12=5x+5-17 | | 7+3x=100 | | 9/2=-8/9k | | 3x-2+4x=2x-8 | | 3(q-p)=q | | 4a=8a | | 45=(3*x)+(x-5) | | 11=n+6 | | z/7-6-5 | | (x^3)-x+5=41 | | 3x+-15=5x+1+-17 | | 2(a-m)=7-a | | 345*0.006= | | 3a=7+2m | | 5x-6y=73 | | 75ML= | | M-5-6m=o | | 2x-6/7 | | 35ab^2-15ab= | | -y^2+y+2=0 | | 5x-2y=33 | | 5.6kg= | | 35=a-32 | | 0=-0.005x^2+2x+5 | | 4(-x+3)=20 | | (54x^8)^(1/3) | | 5x-1=4x+8 | | 4x-7(x-12)=69 | | 1.3x+4.7=12.5 | | X^4+4x^3-2x^2-17x-6=0 | | x+3y+5xy=45 |